Penerapan Pembelajaran Kooperatif Tipe The Two Stay Two Stray Untuk Meningkatkan Kemampuan Komunikasi dan Pemahaman Konsep pada Pembelajaran IPA di Kelas V SDN 32 Bengkulu Tengah - Shinta Widya Nofianti (UNIB Press, 2022)
The purpose of this study is to improve the communication skills and understanding of students' concepts. This research is a class action. The subjects of this study were fifth grade students of public primary schools 32 Central Bengkulu which numbered 24 students. Data was collected through observation and test results. Data is processed by using the percentage of student success in classical and percentage of individual student's success. The results of this study indicate the application of cooperative learning model type TSTS can improve communication skills and understanding of the concept, students of class V public primary schools 32 Central Bengkulu. Improvement of communication skills through cooperative learning model type TSTS cycle I was 33.3%, cycle II was 62.5% and cycle III was 83.3%. Enhancement the understanding of students' concepts through cooperative learning models of the TSTS type in the second cycle was 37.5%, the second cycle was 66.7% and the third cycle was 95.8%, thus the application of the TSTS type of cooperative learning model can improve communication skills and conceptual understanding. The recommendation of this research is that teachers can use good learning method and to actively involve students in learning in order to improve their communication skill and students' concept understanding to be better